Human Resource Performance Improvement Model Design (Case Studi in the Biggest Central Java Automotive Company) - Bayu Setyo Nugroho (Admisi dan Bisnis, 2021)
Not achieving job targets at the Company is caused by non optimal performance of Human Resources at the Company. This research aims to design a model for improving human resource performance through an analysis of the influence of teamwork, knowledge sharing, and innovation capability. In addition, it aims to describe and analyze leader supervision support to moderate the effect of innovation capability on improving Human Resource Performance. The Research was conducted using survey method that is distributing questionnaires to the aftersales employees of PT. Nasmoco Semarang. Hypothesis testing through multiple regression analysis was performed using Statistical Package Social Science (SPSS). The results of the analysis show that teamwork, knowledge sharing, and innovation capability have a positive effect on human resource performance. In addition, leader supervision support moderates the influence of innovation capability on improving human resource performance. The empirical findings indicate that in order to improve human resources performance, leader supervision support is needed to moderate innovation capability towards the human resource performance improvement model design